2019
DOI: 10.1111/1751-7915.13486
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Rhodopseudomonas palustris population dynamics on tobacco phyllosphere and induction of plant resistance to Tobacco mosaic virus

Abstract: Summary Although many biocontrol bacteria can be used to improve plant tolerance to stresses and to promote plant growth, the hostile environmental conditions on plant phyllosphere and the limited knowledge on bacterial colonization on plant phyllosphere minimized the beneficial effects produced by the biocontrol bacteria. Rhodopseudomonas palustris strain GJ‐22 is known as a phyllosphere biocontrol agent. In this paper, we described detailed processes of strain GJ‐22 colony establishment at various colonizati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Recently, Shen and his team successfully used phage treatment to decrease the incidence of disease of tomato (Wang et al ., 2019), but the use of phage biocontrol is still poorly studied. Many microbes have been reported as biocontrol agents, for example, Pseudomonas isolated from maize rhizospheres and Rhodopseudomonas palustris colonizing tobacco phyllosphere (Costa et al ., 2006; Su et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Shen and his team successfully used phage treatment to decrease the incidence of disease of tomato (Wang et al ., 2019), but the use of phage biocontrol is still poorly studied. Many microbes have been reported as biocontrol agents, for example, Pseudomonas isolated from maize rhizospheres and Rhodopseudomonas palustris colonizing tobacco phyllosphere (Costa et al ., 2006; Su et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that PNSB play a role in plant disease control by mitigating biotic stresses. Su and colleagues reported that preinoculation of R. palustris GJ-22 (isolated from activated sludge) on tobacco could elevate plant immunity during subsequent tobacco mosaic virus (TMV) infection and reduce the infection rate of TMV on leaves [73][74][75]. R. palustris KTSSR54 (isolated from Kan-Tulee peat swamp forest, Thachana district, Surat-Thani Province, Thailand) was shown to protect rice from infection by fungal pathogens, particularly those cultivated in acidic soils [76,77].…”
Section: Plant Growth Promoting (Pgp) Traits Exerted By Pnsb On Cropsmentioning
confidence: 99%
“…PGPR-elicited ISR enhances the defensive capacity of host plants and reduces damage from pathogens [140]. Su and colleagues reported that inoculating R. palustris GJ-22 onto tobacco (Nicotiana benthamiana) leaves could induce ISR to TMV [73,74]. The abundance of TMV was reduced to a remarkable extent, the activities of defensive enzymes were enhanced and the transcripts of pathogenesis-related (PR) genes were upregulated [73,74].…”
Section: Pnsb As Biological Control Agentsmentioning
confidence: 99%
“… Ge and Zhang (2019) reported that Rhodopseudomonas palustris G5 could exert beneficial effects on cucumber seedling growth and salt tolerance via indole-3-acetic acid (IAA) and 5-aminolevulinic acid (ALA) production. In addition, a R. palustris strain, GJ-22, was investigated for its biocontrol ability of triggering induced systemic resistance (ISR) against tobacco mosaic virus (TMV) in tobacco plants, and this paper also identified the crucial aggregation stage of GJ-22 strain colonization in the initiation of ISR priming in the plant ( Su et al, 2019 ). In our previous study, two IAA-producing strains of R. palustris (PS3 and YSC3) were isolated from paddy fields in Taiwan and PS3 strain exerted plant-growth promoting effects in enhancing shoot fresh weight and the plant nitrogen use efficiency (NUE) of Chinese cabbage in soil pot system ( Wong et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%